Surface electromyographic (sEMG) activity of the suprahyoid and sternocleidomastoid muscles in pitch and loudness control - Wang, Feifan; Yiu, Edwin M.-L. (Frontiers in Physiology, 2023)
Purpose: This study set out to determine the contributions of the suprahyoid and sternocleidomastoid (SCM) muscles in changing pitch and loudness during phonation among vocally healthy populations. Method: Thirty-nine participants were first recruited, and twenty-nine of them who passed the screening test (Voice Handicap Index [VHI]-10 score ≤ 11, auditory-perceptual voice rating score ≤ 2) were finally selected (mean age = 28.2 years). All participants were measured for their surface electromyographic (sEMG) activity collected from the bilateral suprahyoid and SCM muscles when producing the vowel /a/, /i/, and /u/ in natural (baseline) and at different pitch (+3, +6, -3, -6 semitones) and loudness (+5, +10, -5 dB) levels. Linear mixed-effects models were performed to determine the influencing factors on the root-mean-square percentage of maximal voluntary contraction (RMS %MVC) value of the sEMG signals. Results: Compared with the baseline, a significant decrease of RMS %MVC was found in the suprahyoid muscles during overall phonations of lower pitches (-3 and -6 semitones) and loudness (-5dB). However, no significant change was detected when producing speech at higher pitch (+3 and +6 semitones) and loudness (+5 and +10dB) levels. Among the three vowels, /i/ demonstrated significantly higher RMS %MVC than those of /a/ and /u/. The SCM muscles, however, did not show any significant change in the RMS %MVC values among different vowels in relation to the pitch and loudness changes. When the muscles were compared across the two sides, significantly higher RMS %MVC was found in the right side of the suprahyoid (in pitch and loudness control) and SCM (in pitch control) when compared to the left side. Conclusions: The suprahyoid muscle activities were significantly decreased when producing lower pitches and intensities compared to the natural baselines. The production of sustained /i/ required significantly more suprahyoid muscle activities than those of /a/ and /u/. The SCM muscles did not show much sEMG activity in any of the pitch and loudness levels, which could be used potentially as the calibration or normalization of peri-laryngeal sEMG measurement. The findings also showed a tendency for bilateral asymmetry in the use of suprahyoid and SCM muscles.